Azas Sosial-Budaya, Organisatoris, dan Iptek dalam Pengembangan Kurikulum Pendidikan Agama Islam Multikultural di MTs. Ma’arif I Teluk Jati Dawang Tambak Bawean - Nur Syarifuddin; Khoiriyah (Indonesian Journal of Humanities and Social Sciences, 2020)
Multicultural Islamic Education aims to place multiculturalism as the goal of education with an inclusive, democratic and humanist character based on the Qur'an and Hadith. If multiculturalism is used as the goal of Islamic education, then it can become a new glue for tearing apart the integration of the nation. This research is a field research with a culinary method that seeks to explain multicultural education in MTs I Telukjati dawang Tambak Bawean. The results showed that multicultural education at MTs I Telukjati Dawang Bawean showed multicultural education that occurred due to the existence of social principles, the culture of the local community, mature organization, and adaptation to the mining of science and technology